DECISION SUPPORT SISTEM DESIGN TO DETERMINE TOTAL BLOOD INVENTORY AND TOTAL BLOOD DONORS EVENT - FAUZI NIM: 94515303, MUCHAMMAD
Data on the annual report at PMI Bandung in 2013 Ã‚Â– 2016 shows 72.7% experienced excess stock of blood. Excessive and expired blood supplies should be destroyed. The cost of destruction per bag of blood is about Rp 40.000 / kg which is managed by medical waste treatment services. It means that in the overstock phase in every month PMI Bandung experiences waste and needs inventory control to do. Inventory control is the activity of making decision to determine the amount of inventory. This research explains how to design Decision Support System (DSS) to determine the amount of blood supply and blood donor deployment schedule. The goal is to develop a DSS flow chart, identify DSS needs, design the concept, operation, and tool of DSS, test and analyze the DSS implications. This research was started by reviewing inventory system at PMI Bandung, arranging DSS flow chart, identifying DSS need, designing DSS concept, designing DSS operation and tool, testing and analysing DSS, and making conclusion and suggestion. DSS is divided into data management subsystem, model management subsystem, interface subsystem, and knowledge management subsystem. However, this study does not require knowledge management subsystem. The method used in the data management subsystem is SADT (System Analysis and Design Technique) approach. DSS model management subsystem designed by Microsoft Excel simulation model with Algorithm Model of Optimization of Inventory Management formula, DSS interface management subsystem used is SDLC (System Development Life Cycle) which is applied to VBA (Visual Basic Application) Microsoft Excel. Test results on DSS applications by users, DSS can run well. But there are two unmet needs on non-functional needs. Those are flexibility and security.